Determinan Perilaku Makan Cepat Saji (Fast Food) Pada Remaja Menurut Social Cognitive Theory (SCT): Studi Literatur Tahun 2021-2025 - Alyda Kausy (Barongko: Jurnal Ilmu Kesehatan, 2026)
The eating habits of today's youth have shifted to fast food, which is practical, tasty, and easily accessible through food delivery and social media. However, this carries the risk of causing obesity, diabetes, hypertension, and other health problems. Social Cognitive Theory (SCT) emphasizes the relationship between individual factors (knowledge, attitudes, motivation/intensity, self-efficacy, self-regulation, taste preferences) and environmental factors (family support, peers, socioeconomic status/allowance, physical environment/media access, and gender). According to open access journal collection methods from Google Scholar and PubMed (2021–2025), the conclusion is that environmental variables such as social media access (p<0.05 in several studies), pocket money, and social support have a greater influence on fast food consumption than individual variables. With more dominant platforms such as Instagram serving as a hub for food advertising and trends.